Analisis Kadar DO (Dissolved Oxygen) Pada Air Selokan Yang Ada Di Jalan Teknik Kimia, Keputih, Kec. Sukolilo, Kota Surabaya - Nurul Aliya; Shresy Febi; Annisaa Maheswari; Cinta Aldania; Denny Oktavina Radianto (KOLONI, 2023)
Oxygen has the ability to oxidize with contaminants such as organic components so that these contaminants are not harmful. Oxygen is also needed by microorganisms, both aerobic and anaerobic in metabolic processes. This type of research is the observation of the results of the Liquid TAPL practicum which aims to determine the analysis of DO levels in water at the Surabaya State Shipping Polytechnic. In the practicum that has been carried out, namely the analysis of Dissolved Oxygen (DO) which has the aim of determining the level of dissolved oxygen in water. In determining dissolved oxygen levels, it is necessary to pay attention to the method of sampling so that the measured oxygen content is in accordance with that contained in the waste. The Winkler bottle is put into the waste water to fill the bottle and when closing the bottle make sure the bottle is still in the waste water, so that there is no contact between the sample and the air which can cause diffusion of oxygen from the air into the sample. Based on government regulation No. 80 of 2001 it can be seen that the sample water used is classified as safe from the DO content present in the water, which is 72 mgO2/L. The water is classified as safe to use. Keywords: DO, Dissolved Oxygen, Water